Targeting in social programs avoiding bad bets, removing bad apples - Schuck, Peter H. (Brookings Institution Press, 2006)
"Provides a framework for analyzing the challenges involved in defining bad bets and bad apples and discusses the safeguards that any classification process must provide. Examines public schools, public housing, and medical care and proposes policy changes that could reduce the problems these two groups pose in social welfare programs"--Provided by publisher.